Application of Ecoenzymes from Various Fruit Peels on the Growth and Yield of Tomato Plants (Solanum lycopersicum L.) - Niken Ledi Andra; Zuyasna Zuyasna; Bakhtiar Bakhtiar (Jurnal Agrosci, 2026)
Background. Tomato production is unstable due to declining soil fertility. Ecoenzymes from fruit peels can be a sustainable agricultural alternative to reduce excessive chemical use. This research was conducted at Experimental Garden 1, Faculty of Agriculture, Syiah Kuala University, Darussalam, Banda Aceh, from June 1, 2025, to April 24, 2026. Aims. The objective of the study was to determine the effect of applying an ecoenzyme derived from a mixture of fruit peels on tomato plant growth and yield. Methods. The study was conducted using a non-factorial randomized block design with 7 treatments and 3 replications, yielding 21 experimental units. Each experimental unit consisted of 4 plants, and a total of 84 tomato experimental units. Result. Ecoenzymes from various fruit peels had a very significant effect on stem diameter at 15 DAP and had no significant effect on plant height at 15, 30, and 45 DAP, stem diameter at 30 and 45 DAP, number of productive branches at 50 DAP, flowering age, number of fruits per plant, fruit weight per plant, fruit diameter, and fruit length. Conclusion. Application of 10 mL-1 of E3 resulted in the best number of productive branches, while E2 produced the best number of fruits per plant, fruit weight per plant, and fruit length.